Comparative Study Of The Utility Of Electron Ionization And Chemical Ionization Mass Spectrometry For Confirmation And Quantification Of Stimulants In Urine - Almeer, Muna Ahmad M A (2013)
An analytical procedure for the detection of stimulants in urine using gas chromatography-mass spectrometry (GC-MS) is one of the analytical challenges facing anti-doping laboratories. The use of derivatising reagents for the target compounds will provide better peak shapes, reduce the polarity and enhance the gas chromatographic properties, providing a good separation and mass spectra with high abundance for both identification and quantitative analysis, thus enhancing the detectability of a compound. Silylation, acylation and alkylation reactions are the most effective and common derivatization methods that are used for the GC. This research was focused on five banned stimulants from the WADA prohibited list which were amphetamine, methamphetamine, ephedrine, methylephedrine and cathine. When these compounds were derivatised with various derivatising reagents the limits of detection can be lowered considerably. Traditional GC/MS using electron impact ionisation suffers from product of low mass fragment ions making confirmation of these analytes difficult. When these derivatised compounds were analysed using chemical ionisation (CI) in the GC-MS, the protonated ion [M+H]+ as well as the [M+29]+ and [M+41]+ ions were obtained to be used as confirmatory ions. This research showed that using two steps derivatization by MSTFA followed by MBTFA and analysis using chemical ionisation (CI) can fulfil the identification criteria for qualitative identification of compounds in line with the WADA criteria.